How M.MspI and M.HpaII decide which base to methylate. - Mi, S (1992)
The HpaII methylase (M.HpaII) recognizes the sequence CCGG and methylates the inner cytosine residue. The MspI methylase (MspI) recognizes the same sequence but methylates the outer cytosine residue. Both methylases have the usual architecture of 10 well-conserved motifs surrounding a variable region, responsible for sequence specific recognition, that is quite different in the two methylases. We have constructed hybrids between these two methylases and studied their methylation properties. A hybrid containing the variable region and C-terminal sequences from M.MspI methylates the outer cytosine residue. A second hybrid identical to the first except that the variable region derives from the M.HpaII methylates the inner cytosine residue. Thus the choice of base to be methylated within the recognition sequence is determined by the variable region.